2014
DOI: 10.1007/s00125-014-3294-9
|View full text |Cite
|
Sign up to set email alerts
|

GAD autoantibody affinity in schoolchildren from the general population

Abstract: Aims/hypothesis Subtyping GAD autoantibody (GADA) responses using affinity measurement allows the identification of GADA-positive children with a family history of type 1 diabetes who are at risk of developing diabetes. Here, we asked whether GADA affinity is a useful marker to stratify the risk of type 1 diabetes in GADA-positive schoolchildren from the general population. Methods GADA affinity was measured by competitive binding experiments with [ 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…All discordant samples, except one, used in the present study were obtained from long‐standing patients with type 1 diabetes. As it has been reported that GADA affinity remained relatively constant for >10 years in GADA‐positive non‐diabetic schoolchildren, the duration of type 1 diabetes might not affect GADA affinity. However, it needs to be confirmed whether GADA affinity remains constant after the onset of type 1 diabetes using follow‐up samples.One limitation of the current study was that it was a cross‐sectional study with a relatively small sample size, and did not have data on insulin secretory capacity.…”
Section: Discussionmentioning
confidence: 85%
“…All discordant samples, except one, used in the present study were obtained from long‐standing patients with type 1 diabetes. As it has been reported that GADA affinity remained relatively constant for >10 years in GADA‐positive non‐diabetic schoolchildren, the duration of type 1 diabetes might not affect GADA affinity. However, it needs to be confirmed whether GADA affinity remains constant after the onset of type 1 diabetes using follow‐up samples.One limitation of the current study was that it was a cross‐sectional study with a relatively small sample size, and did not have data on insulin secretory capacity.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, it is believed that the bridging conformation favors the recognition of high-affinity antibodies, contributing to the good specificity [14]. Given that researches say that the existence of high-affinity GADA is more closely associated with the progression of type 1 DM [15,16], the possible high disease activity in GADA-ELISA-positive and GADA-RIA-positive SPIDDM is easily understandable.…”
Section: Discussionmentioning
confidence: 99%
“…Our addition of an N-terminal methionine to GADA (96-585) to allow protein expression is unlikely to have affected antibody binding as it is neither highly charged nor bulky. The inclusion of affinity measurements may also help to identify GADA-positive individuals who are at increased risk of diabetes progression (12,17). The potential for truncated GAD 65 labels to identify patients with slowonset autoimmune diabetes in adults with a clinical presentation of type 2 diabetes also needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%